Role Expectation and Role Performance of Tribal and Non- tribal Women Sarpanchs towards Rural Development - Kumari Jyoti; M. L. Sharma (Indian Journal of Extension Education, 2023)
The present study was conducted during the year 2015-16 in Bilaspur district of Chhattisgarh, state of India to compare and analyse the role performance of tribal and non- tribal women sarpanchs. Out of 645 Gram Panchayat, 336 Gram Panchayat were having women sarpanchs, from which one-third panchayats viz. 112 were randomly selected for the collection of data. Data was collected from the 112 respondents which were further divided into two groups namely Tribal (56 women sarpanchs) and Non- tribal (56 women sarpanchs) respondents of the given district. Suitable statistical tool were used to analyze the data. The study depicts that as a planner, overall performance was maximum (78.57%) for reconstruction of panchayat bhawan. As an administrator, overall performance was highest (71.42%) towards provision for drinking water. As a communicator, overall majority (55.35%) worked for agricultural technology. As a representator, overall respondents represented maximum (59.82%) as an opinion leader. As an initiator, majority of all respondents (67.85%) worked for group organisation. As a harmonizer, overall majority (67.85%) focused towards negotiation. As a helper, the majority (57.14%) tried to fulfil the village needs. As an executer, majority (51.78%) executed for opening higher education institute at village itself. As group organizer, majority (83.08%) worked for self dependence. As a motivator, majority (70.53%) motivated for democracy. The study revealed that majority of the respondents (41.96%) had low performance towards rural development. Overall role performances of tribal respondents were only 21.51 per cent whereas in case of non- tribal respondents, it was 43.57 per cent.